The accelerated waning of immunity and reduced effect of booster in patients treated with bDMARD and tsDMARD after SARS-CoV-2 mRNA vaccination - Tobudic, Selma; Simader, Elisabeth; Deimel, Thomas; Straub, Jennifer; Kartnig, Felix; Heinz, Leonhard X.; Mandl, Peter; Haslacher, Helmuth; Perkmann, Thomas; Schneider, Lisa; Nothnagl, Thomas; Radner, Helga; et al. (Frontiers in Medicine, 2023)
Abstract: Objectives: To assess the duration of humoral responses after two doses of SARS-CoV-2 mRNA vaccines in patients with inflammatory joint diseases and inflammatory bowel disease and booster vaccination compared to healthy controls. To analyze factors influencing the quantity and quality of the immune response. Methods: We enrolled 41 patients with rheumatoid arthritis (RA), 35 with seronegative spondyloarthritis (SpA) and 41 suffering from inflammatory bowel disease (IBD), excluding those receiving B-cell depleting therapies. We assessed total anti-SARS-CoV-2 spike antibodies (Abs) and neutralizing antibody titers 6 months after two and then after three doses of mRNA vaccines compared to a healthy control (HC) group. We analyzed the influence of therapies on the humoral response. Results: Patients receiving biological or targeted synthetic disease modifying antirheumatic drugs (b/tsDMARDs) showed reduced anti-SARS-CoV-2 S Abs and neutralizing antibody titers compared to HC or patients receiving conventional synthetic (cs)DMARDs 6 months after the first two vaccination doses. Anti-SARS-CoV-2 S titers of patients with b/tsDMARDs declined more rapidly, leading to a significant reduction in the duration of vaccination-induced immunity after two doses of SARS-CoV-2 mRNA vaccines. While 23 percent of HC and 19 percent of patients receiving csDMARDs were without detectable neutralizing antibodies 6 months after the first 2 vaccination doses, this number was 62 percent in patients receiving b/tsDMARDs and 52 percent in patients receiving combination of csDMARDs and b/tsDMARDs. Booster vaccination led to increased anti-SARS-CoV-2 S Abs in all HC and patients. However, anti-SARS-CoV-2 S Abs after third vaccination were lower in patients receiving b/tsDMARDs alone or in combination with csDMARDs compared to HC. Conclusions: Patients receiving b/tsDMARDs have significantly reduced Abs and neutralizing antibody titers 6 months after mRNA vaccination against SARS-CoV-2. This was due to a faster decline in antibody levels, indicating a significantly reduced duration of vaccination-induced immunity compared to HC or patients receiving csDMARDs. In addition, they display a reduced response to a third vaccination, warranting earlier booster vaccination strategies in patients under b/tsDMARD therapy, according to their specific antibody levels.